The Legal Strength of Home Ownership Credit Agreements During Covid 19 - Sumarno Sumarno (Budapest International Research and Critics University, 2021)
At this time, during the COVID-19 pandemic, the government's role in meeting the community's needs for housing is urgently needed in providing funds and providing initiatives in housing development efforts. The presence of the Home Ownership Credit system is very much needed by people whose economic income is in the small and medium levels. During this pandemic, banking is one of the sources for obtaining funds which is considered easy and fast for some people in terms of needing funds to meet their needs, such as in utilizing funding from banks in the Home Ownership Credit facility. Each granting credit, there will be rights and obligations. Banks can only consider granting credit if the applicant is a legal subject, because the legal subject is a supporter of rights and obligations, meaning that they can receive rights and be charged with obligations. This study describes the legal arrangements in Home Ownership Loans during the covid 19 pandemic, to find out the rights and obligations of the parties in the Home Ownership Loan agreement, as well as to find out efforts to settle defaults in the Home Ownership Loan agreement. This research was obtained from secondary data, namely library research, namely by collecting references related to the object or research material. Article 1754-1769 is one of the forms of loan-borrowing agreement. By the agreement that has been stated in the credit agreement, each party will obtain its rights and obligations. What is the right of the debtor is the obligation of the bank, and what is the obligation of the debtor is the right of the bank. The implementation of the Home Ownership Credit agreement is made based on a free agreement with the meaning that the agreement can be made freely. Any form of agreement is made between two parties who capable of acting by law to carry out an achievement that does not conflict with the applicable legal rules, morality, and public order, in agreeing to the provision of credit loans, the bank needs to pay attention to the restrictions regulated by the applicable laws and regulations.